Robust mesoporous bimetallic yolk–shell catalysts for chemical CO2 upgrading via dry reforming of methane. Issue 4 (19th June 2018) - Price, Cameron-Alexander Hurd; Pastor-Pérez, Laura; Ramirez Reina, Tomas; Liu, Jian
Abstract : A new generation highly efficient and stable mesoporous ZnO/Ni@silica yolk–shell catalyst is designed for chemical CO2 recycling, to solve the coking and sintering issues of traditional catalysts. Abstract : Here, we report the synthesis of mesoporous ZnO/Ni@ m -SiO2 yolk–shell particles. The unique ZnO/Ni@ m -SiO2 catalysts demonstrate impressive resistance to sintering and coking for dry reforming of methane (DRM). They also display long term stability with high levels of conversion and selectivity, making this catalyst promising for chemical CO2 upgrading.